The Role of Vaccination in Prevention of Foodborne Disease in Children: A Systematic Review - Manullang, Frenky Sorimuda; Anto, Endy Juli (Indonesian Journal of Medicine, 2025)
Background: Foodborne diseases pose a significant global health challenge, particularly for children in developing countries. Vaccination has emerged as a crucial strategy in controlling these diseases. This review examines the effectiveness and safety of foodborne disease vaccines in children based on recent literature. Subjects and Method: This systematic review was conducted using Google Scholar, PubMed, and WHO websites with the keywords "vaccine" and "foodborne disease". Peer-reviewed articles from the past 10 years were analyzed using a narrative synthesis approach. Results: This review identified significant developments in vaccines for rotavirus, cholera, typhoid, and candidate vaccines for Shigella, ETEC, and norovirus. Rotavirus vaccines demonstrated positive impacts in reducing hospitalization rates and deaths due to diarrhea, although effectiveness varied across populations. Inactivated oral cholera vaccines showed protection rates of 52-62% over the first two years. Typhoid vaccines showed potential in reducing disease burden in endemic areas. Development of Shigella, ETEC, and norovirus vaccines is ongoing with promising initial results. Conclusion: Significant progress has been made in developing foodborne disease vaccines, but efforts are needed to improve global vaccination efficacy and coverage. Further research is required to optimize vaccine formulation, delivery strategies, and long-term evaluation across various target populations.